Proteomic Analysis Provides Insights Into the Therapeutic Effect of GU-BEN-FANG-XIAO Decoction on a Persistent Asthmatic Mouse Model - Liu, Li-wei; Xing, Qiong-qiong; Zhao, Xia; Tan, Min; Lu, Yuan; Dong, Ying-mei; Dai, Chen; Zhang, Yang (Frontiers in Pharmacology, 2019)
Gubenfangxiao decoction (GBFXD) is a traditional Chinese medicine based on a combination of Yu-Ping-Feng-San and Erchen decoctions. GBFXD has been widely used for decades in treating asthma at the Affiliated Hospital of Nanjing University of Chinese Medicine. Previously, GBFXD was found to reduce lung inflammation and airway remodeling; however, the underlying mechanism remains unknown. In this study, the effects of GBFXD on asthmatic mice were evaluated based on pathology and lung function; airway hyperresponsiveness (AHR) and pathology were compared among the two different mouse models utilized. Furthermore, the mechanism of action of GBFXD on asthmatic mice was analyzed using iTRAQ labeling technology combined with ingenuity pathway analysis (IPA). Modeling analysis of pre- and post-treatment proteins identified 75 differentially expressed proteins. These proteins were related to B-cell development, calcium-induced lymphocyte apoptosis, antigen presentation, and Th1 and Th2 activation pathways. Moreover, 68 differentially expressed proteins were identified in the GBFXD treatment group compared with the model group. Upstream regulatory factors predicted that interleukin (IL)-4 (necessary for inducing polarization of type 2 [M2] macrophages), cyclooxygenase, and prostaglandin E2 are significantly elevated in the model group. Based on IPA analysis, it was concluded that several pathways, including mitochondrial dysfunction and oxidative phosphorylation, are closely associated with the therapeutic effects of GBFXD in asthma. Moreover, the differential expression of several proteins, including the M2 markers, MRC1, ARG1, Retnla, Chil3, and CHIA, were validated by western blotting, confirming that GBFXD can reduce airway inflammation, which fits the pattern of an alternative M2 activation state, andattenuate AHR. Overall, our findings indicate that GBFXD significantly suppresses M2 macrophage polarization, providing further insights into the mechanism underlying the protective effects of GBFXD.